2022
DOI: 10.1371/journal.pone.0270977
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and accurate method for estimating the erythrocyte sedimentation rate using a hematocrit-corrected optical aggregation index

Abstract: Although both the erythrocyte sedimentation rate (ESR) and optically measured erythrocyte aggregation parameters are affected by the hematocrit, this interaction is not considered by the method used to estimate ESR that considers aggregation parameters. In this study, we investigated the relationship between the ESR obtained by the Westergren method and that obtained with an aggregation parameter, namely, the aggregation index (AI) of multiple hematocrit values and fibrinogen-spiked samples with an analysis ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…The Ht‐corrected HAI of the erythrocyte aggregation parameter AI obtained from the 5‐s syllectogram measured by our instrument was defined by Equation ( 6 ). 18 We reported that V s , obtained by dividing the observed V e by the hindered settling coefficient, agrees well with the value expressed in the following regression equation (Equation ( 7 )) using HAI. Here, a and b are coefficients and c is the settling velocity in the absence of aggregation, that is, V s .…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…The Ht‐corrected HAI of the erythrocyte aggregation parameter AI obtained from the 5‐s syllectogram measured by our instrument was defined by Equation ( 6 ). 18 We reported that V s , obtained by dividing the observed V e by the hindered settling coefficient, agrees well with the value expressed in the following regression equation (Equation ( 7 )) using HAI. Here, a and b are coefficients and c is the settling velocity in the absence of aggregation, that is, V s .…”
Section: Methodssupporting
confidence: 82%
“… 6 , 18 The other is that ESR is Ht dependently decreased due to the effect of hindered settling. 19 , 20 In our previous report, 18 we investigated the effect of Ht and analysis time on an aggregation parameter, namely the aggregation index (AI) determined from the syllectogram, and demonstrated that the effect of Ht on the AI measured over a 5‐s interval could be corrected as the Ht‐corrected AI (HAI) for samples with added fibrinogen. The sedimentation velocity obtained by eliminating the effect of hindered settling could be expressed by the exponential function of the HAI obtained from the 5‐s syllectogram.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously reported device (MEK-1305; Nihon Kohden Corporation, Tokyo, Japan) was used to measure the syllectogram [17]. To dissociate aggregated RBCs, 60 L of blood was flowed at a shear rate of 335 s -1 through a glass cell (cross-sectional inner dimension, 0.8 × 0.8 mm) at 37 • C, and then the flow was abruptly stopped.…”
Section: Rbc Aggregation Measurementsmentioning
confidence: 99%
“…The AI is estimated from the intensity of the blood flow image during the turn-off blood flow period [ 23 ]. More recently, Watanabe et al suggested hematocrit-corrected aggregation index for comparative study of erythrocyte sedimentation rate [ 27 ]. Kakei et al suggested an electrical impedance spectroscopy for monitoring RBC sedimentation in T-shaped container [ 28 ].…”
Section: Introductionmentioning
confidence: 99%